Widening Access for Home-Educated Applicants to Higher Education Institutions in England - Wheeler, Lucie (International Journal of Educational and Life Transitions, 2023)
There has been a rise in Elective Home Education (EHE) as a result of the global pandemic and with this, an anticipated increase in EHE students applying to Higher Education Institutions (HEIs). With this increase, it is vital institutions acknowledge and prepare for widening accessibility. It is the expectation that institutions are inclusive, and this study opens discussions on the inclusivity of this applicant group and the knowledge exchange and collaboration opportunities to facilitate change. The aims of this study were to identify potential barriers in accessing HEIs for EHE students and to gain insight into the experiences of these participants. This study will create a basis for developing policies and practices to work towards building an inclusive transitional process into HEIs for all students and be instrumental in building bridges between mainstream and alternative education. Through a semi-structured interview with a HEI applicant, an online survey with 3 HEI applicants and 2 staff from admissions teams at HEIs in England, and a document analysis on the HEI websites, it is highlighted that more work is needed on improving the inclusivity at these establishments and further study into accessing EHE students for research purposes should be sought. Recommendations are shared.